Nurse perspectives in the emergency department: The synergy tool in workload management and work engagement. (11th April 2021) - Udod, Sonia; MacPhee, Maura; Wagner, Joan I. J.; Berry, Lois; Perchie, Glen; Conway, Aidan
Abstract: Aim: To explore emergency nurses' perceptions of how a nurse‐driven patient needs assessment tool, the synergy tool, influenced their workload management. Background: Quadruple Aim, particularly the fourth aim of improved staff work experiences, served as the conceptual framework to engage nurses in a participatory action research project. This project took place between 2017 and 2020 in two tertiary care emergency departments in one large Canadian city. Method: This study employed a qualitative descriptive component, focus group interviews and nurse comments on two open‐ended survey questions. Results: Use of the synergy tool heightened nurses' awareness of patients' holistic care needs. Nurses also stated how patient needs assessment data helped them identify unsafe workloads. Conclusions: The synergy tool, adapted for emergency department use by nurses, was a means to engage and empower nurses. Patient needs assessment data from the tool identified staffing gaps, resulting in additional nursing staff for both emergency departments. Implications for Nursing Management: A focus on patient needs assessment can be an effective way to address nurses' workload concerns.